Workplace policies and training in China: evidence from matched employee-employer data. Issue 7 (5th October 2015) - Mishra, Vinod; Smyth, Russell
Abstract : Purpose: – The purpose of this paper is to examine the extent to which workplace policies and practices are related to participation in, and frequency and duration of, workplace training, controlling for worker and workplace characteristics. Design/methodology/approach: – The authors regress variables depicting participation, frequency and duration of workplace training on workplace policies and control variables. In the case of participation in training, the dependent variable is binary; hence, the authors use a logit model. To examine the number of times which employees participate in training and the number of days they spend training the authors use a Tobit model. The Lewbel (2012) method is used to examine whether there is a causal relationship between workplace policies and the frequency, and duration, of training. Findings: – The findings suggest that about half of the workplace policies considered are positively correlated with the incidence and breadth of workplace training. There is also some support for the view that bundling of policies is positively correlated with the provision of workplace training. The Lewbel (2012) results suggest a causal relationship between a bundle of workplace policies and the frequency, and duration, of workplace training. There is, however, no evidence that workplace policies designed to devolve responsibilities to workers and incentivize staff polarizes skills through resulting in more training for professional staff over others. Originality/value: – The authors use matched employer and employee cross-sectional data for Shanghai in China. To this point most studies that have examined the determinants of training use data for Europe or the USA. There are few studies of this sort for countries in other regions and, in particular, developing or transition countries. There are no studies at all on the relationship between workplace policies and practices designed to promote organizational performance and training in developing or transitional countries. This study addresses this gap in the understanding of the factors related to on-the-job training in transitional countries, such as China.